Efficacy and safety of methylphenidate on attention deficit hyperactivity disorder in children with Down syndrome. Issue 8 (20th April 2021) - Roche, M.; Mircher, C.; Toulas, J.; Prioux, E.; Conte, M.; Ravel, A.; Falquero, S.; Labidi, A.; Stora, S.; Durand, S.; Mégarbané, A.; Cieuta‐Walti, C.
Abstract: Background: Attention deficit hyperactivity disorder (ADHD) is a common co‐morbidity that affects up to 44% of children with Down syndrome (DS). There is a need for reliable, good quality research on the use of methylphenidate within this population. The objective of this study is to report our experience regarding the management of ADHD in these children using methylphenidate. Methods: This study is a retrospective observation of 21 children with DS, followed at Jérôme Lejeune Institute between 2000 and 2018. The diagnosis of ADHD was made using the Diagnostic and Statistical Manual of Mental Disorders criteria. Efficacy was measured as response or non‐response on two main symptoms: attention/concentration and hyperactivity/impulsivity. Safety was evaluated by the presence or absence of side effects. Results: Sixteen out of the 21 children (76%) showed improvement with methylphenidate. The average age of treatment onset in responding children was 8 years and 10 months versus 6 years and 3 months in non‐responders ( P  = 0.05). Average dose/weight was significantly different in responders and non‐responders (0.82 vs. 0.54 mg/kg/day, respectively; P  = 0.03). Twelve children out of 21 (57%) experienced side effects; only three experienced side effects severe enough to require treatment interruption. Most common side effects were loss of appetite and difficulties in falling asleep. Conclusion: Methylphenidate was effective and safe in treating ADHD in 76% of cases in children with DS, with few serious side effects to report. Early diagnosis of ADHD is important to improve the quality of life, learning, inclusion and socialisation of children with DS.